A high-throughput S-RNase genotyping method for apple - Elena López-Girona; Deepa R. Bowatte; Maia E. M. Smart; Sydel Alvares; Thyana Lays Brancher; David Chagné; Richard K. Volz (Fruit Research, 2021)
Knowledge of the genotypes for the self-incompatibility locus (S-locus) in apple varieties and in genotypes being used as parents is critical for breeding and commercial production. We present a high-throughput set of molecular markers for the identification of 13 common S-RNase alleles (S1, S2, S3, S5, S7, S8, S9, S10, S20, S23, S24, S25 and S28). This set is composed of seven allele-specific quantitative PCR-based High-Resolution Melting assays and four multi-allelic SSR markers. Validation of these markers was performed using 86 apple accessions, including cultivars with known S-genotypes and recent commercial varieties arising from the Plant & Food Research (PFR) cultivar breeding programme. We also characterized the S-genotypes of 183 genotypes representing some of the most valuable parents within PFR’s cultivar breeding programme. The results of this work demonstrate the practical usefulness of this marker set to provide accurate cross-compatibility information to optimise choice of pollenisers in commercial apple orchard design, and to identify compatible parents and guide parental selection when executing apple breeding programmes, to optimise fruit crop yield and quality.